Second line treatment in recurrent urinary incontinence after the use of mid-urethral tapes. Systematic review and meta-analysis of proportions (2019)
OBJECTIVE: Female urinary incontinence has a prevalence of up to 40%. Stress urinary incontinence is the most frequent type, about 50%. When primary management fails, it is unclear what the behavior should be. This study aims to show the cure rate of the second-line management options described in the literature. MATERIAL AND METHOD: Systematic review of the literature with meta-analysis of proportions. Observational and interventional studies were included in which the different types of management of recurrent/persistent urinary incontinence were evaluated in women who had a mid-urethral tape as primary management. RESULTS: 161 studies were identified and screened, including 29 in the qualitative synthesis and 27 in the quantitative synthesis. Given the high clinical and methodological heterogeneity, an estimation of the cure rate for each type of management was performed, with the following results regarding the total combined cure rate: in the implantation of adjustable tapes of 86% (IC95%: 76.4% -92.1%), the implantation of a second mid urethral tape was 75.1% (95% CI: 68% -81.1%), in the shortening of the previous mid urethral tape was 62.3% (95% CI: 49.1% -73.9%) and finally the implantation of bulking agents was 55.4% (95% CI: 43.2% -67%). We did not find enough studies to perform a quantitative synthesis with respect to: pubovaginal sling, colposuspension and pelvic floor therapy, as well as secondary outcomes. CONCLUSION: The evidence found shows that there may be superiority of the adjustable tapes versus the mid urethral tapes and other included treatments. However, a comparison to statistically corroborate this difference could not be made. These results should be confirmed with multicenter collaborative randomized clinical trials. © 2019 Iniestares, S.A.. All rights reserved.